Effect of three different inoculum levels of root knot nematode Meloidogyne spp. in infection criteria and some growth traits of cucumber (Cucumis sativus L.) - Ismail, Waref M.H. (Journal of Kerbala for Agricultural Sciences, 2022)
The study was conducted to find out the effect of three different levels of root-knot nematode inoculum on cucumber plants. An increase in infection criteria was observed when levels of contamination increased, as the highest number of root-knots, number of females, egg masses, root-knot index and soft root weight on cucumber plants when contaminated with 2000 eggs were recorded. / pot, as it reached 26.33 knots. 2 g/root, 23.00 female and juvenile, 2 g/root, 19.00 egg mass, 2 g/root, 3 root knot index and 11.33 g/plant of soft root weight, respectively, while a gradual decrease in growth characteristics was observed. With an increase in the levels of contamination in the lengths of the shoot and root, the vegetative fresh weight and the number of branches of the plant, the lowest values ​​were recorded in the treatment of contamination with 2000 eggs/pot, which reached 25.33 cm, 15.00 cm, 16.33 g, and 5.66 branches/plant for each of them, respectively compared with in the treatment of control.